2018
DOI: 10.1016/j.tiv.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Transepidermal water loss and skin conductance as barrier integrity tests

Abstract: In vitro skin permeation studies are commonly used in the risk assessment of toxic compound skin exposure. The present study examined the utility of transepidermal water loss (TEWL) and electrical conductance as barrier integrity tests before skin permeation studies in vitro using a large number of skin samples and fentanyl. TEWL and conductance of the skin samples were measured before the permeation experiments in Franz diffusion cells in vitro with a vapometer and low voltage application, respectively. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 35 publications
3
29
0
1
Order By: Relevance
“…This suggests that ER could detect invisibly damaged epithelium, under the conditions employed in the present study. The effect of physical damage on ER was observed previously for esophageal epithelium mucosa [ 28 ] and skin samples [ 25 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This suggests that ER could detect invisibly damaged epithelium, under the conditions employed in the present study. The effect of physical damage on ER was observed previously for esophageal epithelium mucosa [ 28 ] and skin samples [ 25 , 34 , 35 ].…”
Section: Discussionsupporting
confidence: 53%
“…Skin integrity is typically assessed prior to transdermal permeation assays. Among the different methods available, measuring electrical resistance (ER) across the skin has been used since the 1990s [ 22 , 23 ], and is considered to be simple, fast, safe, and cost-effective [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transepidermal water loss (TEWL) was chosen to measure barrier integrity before and after tape stripping in our studies due to the ease of use and because skin TEWL values increase as barrier integrity decreases, presenting a quantitative way to assess barrier disruption [ 54 , 55 ]. TEWL increased by about five times with tape stripping, proving that the skin barrier was significantly disrupted ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Normal hydration levels maintain SC flexibility and its viscoelastic characteristics in addition to facilitating the enzymatic reactions involved in the maturation of corneocytes [ 86 , 87 ]. Destabilization or damage to the skin surface by exposure to physical or chemical agents can cause changes in TEWL and SCH [ 88 , 89 , 90 ]. In this study, the evaluation of these parameters confirmed that APR-ME does not alter sebaceous function nor compromise the integrity of the skin barrier.…”
Section: Discussionmentioning
confidence: 99%